A tale of two strategies higher education and economic recovery in Ireland and Australia - Hazelkorn, Ellen (OECD Publishing, 2011)
The complex effects of the global financial crisis (GFC) have affected countries differently. The concept of stimulus packages to enable economies to withstand its full effects was widespread, as were decisions by several countries to invest in higher education as a means of stimulating the economy while placing workforce development and research on a firmer footing. While the GFC increased awareness of the need to invest in the knowledge economy, governments adopted approaches reflecting their different fundamental priorities. Arguably Ireland was left with little leeway, whereas Australia's far better economic position might have provided an opportunity to invest in higher education through its stimulus packages. This paper examines the policy choices that Australian and Irish governments made both before, and in response to, the GFC to assess how these decisions have prepared higher education for the future